Analisis Daur Hidup Usahatani Jagung Pakan Dengan Mekanisasi Terhadap Gas Rumah Kaca (GRK) Di Desa Tambang Ulang, Kalimantan Selatan - Darmawan, Muhammad Indra; Ilmannafian, Adzani Ghani; Kiptiah, Mariatul; Mawardi, Muhammad Ikhsan (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2024)
The development of maize agricultural in Indonesia continues to increase. Along with this, the potential risks in environmental aspects as GHGs will be even greater. The purpose of this study is to identify and measure GHGs in each process flow of maize agriculture and provide recommendations for efficient mitigation efforts against environmental impacts generated by maize agriculture with a semi-automatic system in Tambang Ulang village. The research method used is field research in Tambang Ulang Village with LCA analysis carried out in four stages, definition of objectives and scope, input and output inventory analysis, environmental impact analysis of inventory, and interpretation of results. GHG measurements are carried out using emission factors and energy coefficients, calculations based on the guidelines of the Intergovernmental Panel on Climate Change. The results showed that the GHG emissions produced in the production per ton of maize were 401.12 kg CO2 eq. The largest GHG emissions are produced by urea fertilization with emissions of 51.38% of the total emissions produced. Mitigation recommendations that can be done to reduce GHG emissions are using types of manure with less N amounts and reducing the use of chemical fertilizers; adding organic fertilizers that are more environmentally friendly; and using legume cover crops and N-fixing bacteria as environmentally friendly N sources.